Temporal and spatial distribution of Araucaria angustifolia (araucariaceae) pollen in Misiones, Argentina. (Boletín de la Sociedad Argentina de Botánica, 2014)
Temporal and spatial distribution of Araucaria angustifolia (Araucariaceae) pollen in Misiones, Argentina. Araucaria angustifolia (Bertol.) Kuntze is a native species of high commercial value that has indiscriminately been exploited and is currently in critical danger. This work represents the beginning of a research program in Aerobiology related to its reproductive phenology, being conducted in Misiones (Argentina). Two types of continuous volumetric samplers were used: one fixed and the other one portable, distributed in 6 sampling points located in the direction of the prevailing winds. The main pollination period in 2010 (90% of total pollen) lasted 30 days, accumulating 23,548 grains. The daily concentration showed a maximum of 10 to 14 hours following the circadian pattern of atmospheric conditions, with minimum values at 22 hours and 6 hours. An occasional small increase of pollen was observed in the evening, which could be ascribed to the local pollen entrainment. The days with higher concentrations coincided with warmer weather conditions, stronger winds and lower relative humidity with respect to the averages for the period. Lower concentrations were noticed in the endpoints bounds of population distribution, indicating limitations in transport. This study represents an advance in the proper management and conservation of the genetic resources of this species